2020
DOI: 10.1097/mat.0000000000001173
|View full text |Cite|
|
Sign up to set email alerts
|

Initial ELSO Guidance Document: ECMO for COVID-19 Patients with Severe Cardiopulmonary Failure

Abstract: Disclaimer: ECMO has, and will certainly continue, to play a role in the management of COVID-19 patients. It should be emphasized that this initial guidance is based on the current best evidence for ECMO use during this pandemic. Guidance documents addressing additional portions of ECMO care are currently being assembled for rapid publication and distribution to ECMO centers worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
318
0
19

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(342 citation statements)
references
References 4 publications
5
318
0
19
Order By: Relevance
“…Second, complications such as myocarditis (8-10) acute myocardial infarction (11), arrhythmias (9), thromboembolic events (12)(13)(14), and heart failure (11,14), have been linked to COVID-19 infection. In some cases, these complications engendered treatment with ECMO (15)(16)(17). Third, reports on cardiovascular side effects of COVID-19 therapies have been published (18)(19)(20), and lastly, the pandemic's consequences regarding non-COVID-19 cardiovascular patients.…”
Section: Discussionmentioning
confidence: 99%
“…Second, complications such as myocarditis (8-10) acute myocardial infarction (11), arrhythmias (9), thromboembolic events (12)(13)(14), and heart failure (11,14), have been linked to COVID-19 infection. In some cases, these complications engendered treatment with ECMO (15)(16)(17). Third, reports on cardiovascular side effects of COVID-19 therapies have been published (18)(19)(20), and lastly, the pandemic's consequences regarding non-COVID-19 cardiovascular patients.…”
Section: Discussionmentioning
confidence: 99%
“…The application of VA-ECMO is indicated when inadequate tissue perfusion has manifested as hypotension and low cardiac output despite adequate intravascular volume [ 5 ]. Bartlett et al [ 6 ] reported ECMO is considered when the situation presenting PaO 2 /FiO 2 <80 lasts longer than 6 h. Our patient suffered from PaO 2 /FiO 2 <78 on FiO 2 290% for 12 h and had a Murray score of 3.5. The patient developed oliguria and her BP decreased below 90/60 mmHg despite the administration of norepinephrine.…”
Section: Discussionmentioning
confidence: 73%
“…The risks and benefits should be weighed to prevent or reduce additional complications, such as the ECLS circuit‐related thrombosis or bleeding that results from the potentially negative interplay between COVID‐19 and extracorporeal devices. However, appropriate patient selection criteria that was addressed by experts and scientific organizations, such as ELSO, may provide significant help with difficult decision‐making 136 . Because it remains a bridging strategy to buy the time toward recovery, ECLS cannot act as the ultimate treatment for the underlying COVID‐19 disease (Figure 4).…”
Section: Perspectives After the Pandemic: “The Aftermath Of The Pandementioning
confidence: 99%